IMPLEMENTATION OF THE TEACHER PROFESSIONAL EDUCATION PROGRAM (PPG) FOR ELEMENTARY SCHOOL TEACHER EDUCATION AT UNIVERSITAS KUNINGAN - Marlina Eliyanti Simbolon; Aldi Nurhadiat Iskandar; Dita Hardiyanti (Indonesian Journal of Learning and Instruction)
This study evaluates the implementation of the Teacher Professional Education Program (PPG) at Kuningan University with a focus on its role in improving the quality of PGSD teachers. Using qualitative methods, data were collected through literature reviews, questionnaires, and interviews with relevant stakeholders. The results of the study show that PPG succeeds with a high graduation rate; Of the 150 participants, 147 passed the Knowledge Test (UP), 149 passed the Achievement Test (Ukin), and 147 passed the PPG Student Competency Test (UKMPPG). Success factors include effective communication, adequate resources, positive disposition, and smooth bureaucracy. However, this study has limitations, including a limited sample at the University of Kuningan. The conclusion shows that PPG improves the competence of PGSD teachers and recommends a follow-up study to compare the implementation of PPG in various universities. This research contributes to the understanding and management of educational programs in LPTK.